The Influence of Education, Regional Spending, and Infrastructure in Encouraging The Improvement of Village Development Index in Mataraman Regency - Amalia, Holisatul; Iriani, Ririt (MediaTrend, 2025)
Equitable village development is one of the main focuses in achieving inclusive and sustainable national development goals. The Village Development Index (IDM) as a measuring tool for village development used by the Indonesian government is an important indicator in seeing the progress of village development. This studyiiiaims to analyze the effect of education, regional spending, and infrastructure variables on increasing IDM in the Mataraman area, East Java Province. This study uses a quantitative approach with multiple linear regression analysis techniques using the eviews 12 application. The data used are secondary data from the Central Statistics Agency (BPS) and the Ministry of Villages, Development ofiiDisadvantaged Regions and Transmigration (Kemendesa PDTT) in 2018-2022. The results of the study show that education and regional spending have a positive andiisignificant effect on IDM, while infrastructure does not have a significant effect. This study implies that village development policies need to emphasize increasing access to education, regional spending and basic infrastructure to encourage sustainable village development.